THE SPORTS GOODS MARKET IN THE EU - Maja Štrbac (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
There are a number of ways to divide this market sector, but broadly speaking the sports market essentially relates to products used in the pursuit of active team or individual sports. This would include team sports, equipment for fitness, gym, snow sports, equipment for water sports, golf, tennis and skating. There is also the "outdoor" market. This would include camping goods, fishing and horse sports. There are a number of inter- related trends, which impact on the future development of this market sector